PKM PENGELOLAAN BANK SAMPAH BERBASIS KOMUNITAS KELURAHAN BELENDUNG KECAMATAN BENDA KOTA TANGGERANG - Setiadi, Iwan Kresna; Supriadi, Yudi Nur; Wahyudi, Wahyudi; Tristiarto, Yoko; Sugianto, Sugianto (Batara Wisnu : Indonesian Journal of Community Services, 2023)
The waste problem is still a complicated problem due to the lack of public understanding of the impacts caused by waste, the lack of government funds to ensure proper and qualified waste disposal. Another factor that causes the waste problem to become more complicated is the increasing standard of living of the people but not followed by an increase in knowledge about waste and the lack of the community’s role in maintaining cleanliness and disposing of waste in its place. Community Service Activities (PKM) provide empirical ideas for real work to change the community’s paradigm regarding waste that needs to be carried out in a sustainable manner. Educating residents about awareness and skills for waste management by applying the principles of reduce, reuse, recycle and replant (4R) is important in solving waste problems through waste management from its source. A waste bank based on community participation in the Belendung Village is social capital in community-based waste management. Departing from the real problems and conditions of the Belendung Village Garbage Bank regarding waste bank learning to strengthen the implementation of science and technology, real efforts need to be made in providing solutions, through UPN Veteran Jakarta Community Service (PKM) activities through the development of structured and comprehensive waste bank coaching in waste bank management and managerial quality improvement. PKM is held as an empowerment process that intersects with the ability to create. One of the components of this waste management system is the existence of a waste manager who has collected and separated waste (organic and inorganic). The presence of community empowerment in the waste bank movement was moved to experience a general transformation into a movement based on more specific issues, one of which was the Belendung Village Garbage Bank as a forum for PKM activities. The existence of a Waste Bank Management carried out by the KWT Fishing group of Belendung Village is still simple, only in the activity of weighing waste, so the PKM UPN Veterans Jakarta Team will provide training to make activities or activity programs that will be able to increase the entrepreneurial spirit for them. . The hope of this PKM activity is to foster social awareness for the community and be able to manage the Garbage Bank into an activity that can increase income for the group of women from KWT Fishing in the Belendung Village and foster an entrepreneurial spirit